Analisis Peran Guru Dalam Proses Pembelajaran Pada Siswa Kelas III di MI Syuhada Kabupaten Kapuas Hulu - Handayani, Masitah; Imran, Imran; Ramadhan, Iwan; Okianna, Okianna; Alhidayah, Riama (Jurnal Kewarganegaraan, 2022)
This study aims to determine the teacher's role in the learning process for third-grade students at MI Syuhada Nanga Jajang, Pengkadan District, Kapuas Hulu Regency. The method used is a qualitative method with descriptive analysis. This study's data sources were teachers and students of class III MI Syuhada. The data were the observations and interviews with teachers and students of class III MI Syuhada. The results showed that the teacher's role as an educator had been carried out well. It has been proven that it has been found that the teacher provides an example and the teacher guides students during observations and in the results of interviews with teachers and third-grade students of MI Syuhada. The teacher's role as a motivator has been proven to be good, and it has been found that the teacher is a motivator and motivator at the time of observation which is supported by the results of interviews with teachers and third-grade students of MI Syuhada. The teacher's role as a facilitator has been carried out well. It has been proven that it has been found that the teacher provides learning methods and media during observation, and is supported by the results of interviews with the teacher and third-grade students of MI Syuhada.